ZnAl‐Hydrotalcite‐Supported Au25 Nanoclusters as Precatalysts for Chemoselective Hydrogenation of 3‐Nitrostyrene. Issue 10 (31st January 2017) - Tan, Yuan; Liu, Xiao Yan; Zhang, Leilei; Wang, Aiqin; Li, Lin; Pan, Xiaoli; Miao, Shu; Haruta, Masatake; Wei, Haisheng; Wang, Hua; Wang, Fangjun; Wang, Xiaodong; et al.
Abstract: Chemoselective hydrogenation of 3‐nitrostyrene to 3‐vinylaniline is quite challenging because of competitive activation of the vinyl group and the nitro group over most supported precious‐metal catalysts. A precatalyst comprised of thiolated Au25 nanoclusters supported on ZnAl‐hydrotalcite yielded gold catalysts of a well‐controlled size (ca. 2.0 nm)—even after calcination at 500 °C. The catalyst showed excellent selectivity (>98 %) with respect to 3‐vinylaniline, and complete conversion of 3‐nitrostyrene over broad reaction duration and temperature windows. This result is unprecedented for gold catalysts. In contrast to traditional catalysts, the gold catalyst is inert with respect to the vinyl group and is only active with regard to the nitro group, as demonstrated by the results of the control experiments and attenuated total reflection infrared spectra. The findings may extend to design of gold catalysts with excellent chemoselectivity for use in the synthesis of fine chemicals. Abstract : Size‐controlled gold nanocatalysts were prepared from a ZnAl‐hydrotalcite‐ supported thiolated Au25 precatalyst. Residual sulfur and epitaxial interactions between gold and the support stabilized the catalyst against high‐temperature calcination, thereby promoting complete conversion of 3‐nitrostyrene into 3‐aminostyrene with high selectivity for the nitro group.